1974
DOI: 10.1295/polymj.6.537
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Mixtures of Poly(γ-benzyl-L-glutamate) and Poly(γ-benzyl-D-glutamte)

Abstract: It has been reported that there is a special side chain-side chain interaction between the right-handed and left-handed a-helices in the racemic mixture of poly-(r-benzyl glutamate). In this paper physical properties of mixtures of poly(r-benzyl-Lglutamate) and poly(r-benzyl-n-glutamate) are studied. From X-ray diffraction measurements, the reflection characteristic of the regular arrangement of the benzyl group at the end of the side chain was shown to disappear on heating at 97°C and to appear on cooling at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Fukuzawa, et al, 4 reported results of dilatometric measurements in which specific volumes of the racemic form of PBG varied reversibly against temperature with some extent of supercooling on cooling, as is usually observed in crystalline polymers.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Fukuzawa, et al, 4 reported results of dilatometric measurements in which specific volumes of the racemic form of PBG varied reversibly against temperature with some extent of supercooling on cooling, as is usually observed in crystalline polymers.…”
Section: Resultsmentioning
confidence: 93%
“…This reversible change was also observed in viscoelastic, thermal, and dilatometric measurements and ascribed to the breakdown and formation of stacks of the benzene ring. 4 Information on the arrangement of the benzyl groups can be obtained from the results of infrared examination. Tsuboi, et al, 2 have shown that the dichroic ratios observed for absorption bands attributable to the main chain vibrations for the racemic mixture are not different from those of PBLG, while three bands at 1498 cm-1 , 1453 cm-1 , and 697 cm-1 , assignable to vibrations in the phenyl group at the end of the side chain, show stronger dichroism in the Polymer J., Vol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uematsu et al observed this reflection disappears when the sample is heated to some 90°C, and ascribed the disappearance to the disruption of the stack.ing. 4 The present authors also made X-ray and dielectric measurements on mixtures of the o and L polymers, and discussed the results on the basis of the theory of order-disorder transition. 5 • 6 In this paper, we present the results of a dynamic mechanical investigation on mixtures of PBDG and PBLG and provide further evidence for the stacking of benzene rings.…”
mentioning
confidence: 93%
“…8 Uematsu et al reported that the extra reflection peak disappears around 90°C and ascribed this phenomenon to the breakdown of 'stacking structure'. 9 Takahashi et al 6 and Matsushima et al 10 have made dielectric relaxation and X-ray diffraction measurements, respectively and discussed this phenomenon as the order-disorder transition. It is well known that 13 C cross polarization/ magic angle spinning (CP/MAS) NMR is one of the most powerful methods for studying local structures and mobilities of polymers in the solid state.…”
mentioning
confidence: 99%